P-73 Improving palliative dementia care – evaluation of a new education programme. (1st March 2017) - White, Clare; McVeigh, Clare; Foster, Sue; Dunwoody, Lynn; Watson, Max
Abstract : Background: Globally, dementia is a growing healthcare problem. Both the life-limiting nature of the illness and the clinical manifestations of the disease warrant patients and their families being able to access a palliative approach to care. Due to the complex symptomatology associated with dementia, providing optimal holistic care can be challenging and healthcare professionals (HCPs) need the appropriate level of knowledge and skills in both palliative and dementia care. The European Certificate in Holistic Dementia Care (ECHDC) is an 8 week, multidisciplinary home study programme designed to help meet this need. The course was created by palliative and dementia specialists. The aim of this research was to evaluate the effectiveness of the course in improving the knowledge and skills of HCPs regarding a palliative approach to dementia care. Methods: A prospective mixed methods longitudinal cohort study was conducted to evaluate the education program. The first phase incorporated baseline knowledge and self-efficacy assessments prior to commencement of the course. The second phase encompassed post course knowledge and self-efficacy assessments, and focus groups exploring participants' experiences and perceptions of the course in enhancing their knowledge and skills in relation to palliative dementia care. Results: Forty-eight participants completed the course in November 2015, with 43.8% (n=21) completing both phases of assessments across 3 European sites. Average knowledge scores improved significantly from 47.7% to 66.1% (p=0.0005). Self-efficacy (p=0.00005) and overall confidence (p=0.0005) also improved. Twelve HCPs participated in two focus groups across two sites, which identified the overarching theme- the ECHDC enhanced participants practice. Conclusion: This study demonstrated that a multidisciplinary distance learning course significantly improved the knowledge and self-efficacy of HCPs in delivering end of life care to patients with dementia and their families. The course was felt by participants to improve the care they provided for patients.